Alpheus perlas, sp. nov., a new infaunal snapping shrimp from the Pacific coast of Panama (Malacostraca: Decapoda: Alpheidae) - Anker, Arthur; Pachelle, Paulo P.g. (Zootaxa, 2019)
A new snapping shrimp, Alpheus perlas sp. nov., is described based on a single complete male specimen collected on a shallow mudflat at Casayeta Island in the Las Perlas Archipelago, Gulf of Panama. The new species belongs to the large A. edwardsii (Audouin, 1821) species group characterised essentially by the presence of two notches on the major chela palm, with the dorsal notch extending posteriorly on the mesial surface. Within the eastern Pacific members of the A. edwardsii group, A. perlas sp. nov. appears to be morphologically closest to A. latus Kim & Abele, 1988 and A. burukovskyi Anker & Pachelle, 2015. Alpheus perlas sp. nov. does not seem to be specially adapted for digging and may be inquiline of a larger burrowing host, which currently remains unknown.